Peptic ulcer: does it changed identity? - Ye. A. Pyatenko; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate possible changes of peptic ulcer (PU) epidemiology: gender and age of patients, age at disease onset, ratio of the stomach ulcers (SU) to duodenal ulcers (DU), clinical features at relapse of PU, frequency of concomitant digestive diseases. Material and methods. Overall 79 case records of patients with PUD of the stomach (PUS) (16 men, 33 women), PUD of duodenum (PUD) (15 men, 9 women) and PUD of combined localization (1 man and 5 women) were included in the study by continuous sampling method. Symptom frequency at PUD relapse and accompanying changes was estimated independently for male and female groups. Results. At the present time there is a shift of PUS to PUD ratio towards more common stomach ulcer location, increase in female proportion of PU patients and mean patient age at the onset of disease. Epigastric pain that develop in fasting state or after food intake remains to be the leading symptom of PU relapse and is observed at 87.5% of male and 95.7% of female patients. Significant number of patients present with heartburn and belching, that is explained by high frequency of PU to gastroesophageal reflux disease (GERD) combination (in 93.8% of men and 83.0% of women). Positive test for Helicobacter pylori (H. pylori) infection were received in 94.9% of patients. Idiopathic H. pylori-negative ulcers were detected only in 5.1% of patients. Conclusions. The modern trend in the PU clinical course is characterized by shift of typical male to female ratio, as well as PUD to PUS ratio, the high frequency of PU to GERD combination. Most patients were admitted for relapse of PU were positive for H. pylori infection.